Market Segmentation and Product Sustainability of Fast Moving Consumer Goods (FMCG): A Study of Nestle Product in South-East Nigeria - Nnenne Ifechi Adani; Ifeanyi E. Nuel Okoli; Chinenye Maureen Nuel-Okoli (Innovation Business Management and Accounting Journal, 2025)
The study examined the influence of market segmentation on the product sustainability of fast moving consumer goods (FMCG) using Nestle product in South-east Nigeria as a case of reference. The specific objective was to ascertain the extent to which demographic market segmentation, geographic market segmentation, behavioural market segmentation and psychographics market segmentation influence the competitiveness of Nestle product in South-east Nigeria. Descriptive survey research design was adopted in the study, on a sample respondent made up of 323 consumers of Nestlé products across South-east Nigeria. Primary data were collected from the respondents using a structured questionnaire developed in line with 5-point Likert-scale system. The analysis of the research questions was done using descriptive tools such as percentages, mean and frequency analyses. Pearson Product Moment Correlation was used to test the four null hypotheses of the study. The findings revealed the following: demographic market segmentation significantly and positively influences the competitiveness of Nestlé products in South-East Nigeria; geographic market segmentation significantly and positively influences the competitiveness of Nestlé products in South-East Nigeria; behavioral market segmentation significantly and positively influences the competitiveness of Nestlé products in South-East Nigeria; psychographic market segmentation significantly and positively influences the competitiveness of Nestlé products in South-East Nigeria. In conclusion, a multidimensional approach to market segmentation, with particular emphasis on psychographic factors, is essential for maintaining and enhancing the competitiveness of fast-moving consumer goods like Nestlé in the dynamic market of South-East Nigeria. The study recommends that Nestlé’s product development and branding team should endeavour to align all their products with the values and lifestyles of consumers by offering products that resonate with personal values and healthy lifestyle trends, reinforcing the emotional connection with their brand.